3D Animation Making Crafts Monel Jepara - Listyorini, Tri; Umam, Muhamad Khotibul; Riadi, Aditya Akbar (Scientific Journal of Informatics, 2022)
Abstract. Monel Craft is a handicraft that is inherited from generation to generation by the people of Jepara. Monel accessories produced can be in the form of bracelets, necklaces, earrings, rings, and many other accessories. For its manufacturer using a drill, hacksaw, and smoothing machine. Monel marketing is still limited around the city of Jepara. Purpose: This research aims to introduce Monel more broadly with a 3D multimedia approach. So, there is an idea of what Monel is. In general, Monel has a shiny shape and is corrosion-resistant. The price is relative and can be ordered according to our wishes.Methods: The method used in this research is the method of multimedia development.Result: This research produces a 3D animation that is packaged attractively, so that it represents Monel craftsmen to introduce it to the whole community.Novelty: This research combines the multimedia method with the work of local wisdom from the city of Jepara, namely Monel. This research, entitled "Monel Craft 3D Animation", can increase knowledge about how to make it. And can be a medium of education and preservation of cultural arts in Jepara.